Caractérisation de la ferrihydrite authigénique synthétisée sous différentes conditions et en présence ou absence de bactéries. - Thibault, Pierre-Jean. (University of Ottawa (Canada), 2002)
2-ligne ferrihydrite was synthesized under different conditions, then characterized by transmission electron microscopy, by X-ray diffraction and particularly by Mossbauer spectroscopy. Three synthesis media have been investigated: (1) in the presence of Bacillus subtilis bacteria, (2) in the presence of Bacillus licheniformis and (3) abiotic, at different concentrations of iron (1 x 10-3 M, 5 x 10-3 M and 1 x 10-4 M) and different pH, (6, 7, 8 and 9). We have also studied the effects: of two precursor salts in the synthesis (FeCl2·4H 2O and FeNO3·9H2O), of the drying method (wet, air-dried or freeze-dried) and of the aging of the samples. We have found that the presence of bacteria affects the crystallinity and creates structural disorder. At lower iron concentration, the biotic samples show some Fe2+. The concentration and aging variations show opposite trends between biotic and abiotic samples. The type of salt used has an important effect but the pH and the drying method have a much smaller one. The thesis comprises a literature review of the Mossbauer parameters of ferrihydrite.
Keywords: Biogeochemistry.